Survey is based on Synchronized and Asynchronized Approach of MAC Protocols in WSN - Soni Chaurasia (Sensors & Transducers, 2010)
A wireless network is made of spatially distributed autonomous devices. These devices are called sensors. The sensor is used for monitoring physical or environmental conditions. The potential application of wireless sensor network is environmental monitoring, healthcare applications and tactical systems. In this paper focus is on the MAC protocol for WSN. Wireless sensor network is deployed for wide range to send and receive data with the help of medium. Here literature survey of MAC protocol based on the synchronized and asynchronized approach is described which is used to meet different objective like access a medium, statistical channel allocation, spectrum utilization